Historical perspectives on forest policy change in Asia: an introduction - Edmunds, D.; Wollenberg, Eva Karoline (2001)
Forest devolution policies have generated much hope for sustainable development in rural areas of the South. Yet such policies have not always generated economic benefits for the poor, and have seldom transferred substantial decision-making authority to the poorest forest users. We discuss four case studies of the history of devolution policies in Asia that ask why. We draw several conclusions from these cases. Devolution policies will fail to meet the expectations of the poorest forest users unless they address historical ‘holdovers’, particularly ideologies and institutions within government that continue to favor centralized control and elite/subordinate relations at the local level. At the same time, policies must include scope for building capacity at the local level to deal with new forests and new institutional and political conditions. The state can play a role in capacity building, but will succeed only by working collaboration with social movements and NGOs that advocate on behalf of forest users, especially the poor among them. Because addressing holdovers and building capacity are difficult tasks, policies should be organized so that they can be reviewed and reformed in a collaborative fashion on a regular basis.